Legends of the fall [videorecording (Blu-Ray)] - Shilliday, Susan; Witliff, Bill; Zwick, Edward; Herskovitz, Marshall; Pitt, Brad, 1963-; Hopkins, Anthony, 1937-; Quinn, Aidan; Thomas, Henry, 1971-; Ormond, Julia; Horner, James; Harrison, Jim (Columbia Pictures, 2011)
Two sons of a retired army colonel in Montana, lust after their brother's wife. Special features include commentary, deleted scenes, and more.